Community and sociodemographic factors associated with disclosure of sexual orientation and comfort in discussing care needs in primary care: Results from the OutLook Study. - Coleman, Todd A.; Tse, Samson; Gergyek, Lucas; Cameron, Ruth; Coulombe, Simon; Davis, Charlie; Travers, Robb; Wilson, Ciann; Woodford, Michael (Canadian Journal of Human Sexuality, 2024)
Lesbian, gay, bisexual, and diverse sexual orientation minorities are disproportionately represented in the prevalence of adverse health conditions, even in Canada, suggested as one of the more progressive countries when it comes to social acceptance and human rights protections. This highlights the inclusion of sexual orientation identity as a point of consideration when providers interact with patients and to consider facilitating sexual orientation identity disclosure when accessing health care. This study explored factors associated with different facets of sexual orientation disclosure to primary care providers. A cross-sectional survey of sexual orientation minority participants, 16 years or older, living, working, or residing in Waterloo Region was distributed (n = 437). Modified Poisson regression methods modelled (a) comfort sharing sexual orientation with their regular primary care provider (RPCP), (b) disclosure of sexual orientation to their RPCP, and (c) talking to their RPCP about health issues related to their sexual orientation. Increasing outness within one's social network was consistently significant across all three outcomes of comfort, disclosure, and talking about health issues related to sexual orientation. Self-esteem was also identified as salient in comfort and when talking to providers. The authors also observed significant associations between sexual orientation identity and relationship status variables. Findings highlight important factors to consider in discussing and disclosing sexual orientation identity and associated health issues with health care providers. Implications for practice include training new health care providers and providing opportunities for continued education for established providers to ensure appropriate care is provided based on sexual orientation.